Mental Health Problems and Risk of Suicidal Ideation and Attempts in Adolescents - Orri, Massimiliano; Scardera, Sara; Perret, Léa C; Bolanis, Despina; Temcheff, Caroline; Séguin, Jean R; Boivin, Michel; Turecki, Gustavo; Tremblay, Richard E; Côté, Sylvana M; Geoffroy, Marie-Claude (Pediatrics (Evanston), 2020)
Obtaining recent estimates of the prevalence of suicide-related outcomes across adolescence and its associated mental health problems (MHPs) is important for clinical practice. We estimated the prevalence of suicide-related outcomes at ages 13, 15, 17, and 20 years (2011-2018) in a contemporary population-based cohort and documented associations with MHPs throughout adolescence.BACKGROUNDObtaining recent estimates of the prevalence of suicide-related outcomes across adolescence and its associated mental health problems (MHPs) is important for clinical practice. We estimated the prevalence of suicide-related outcomes at ages 13, 15, 17, and 20 years (2011-2018) in a contemporary population-based cohort and documented associations with MHPs throughout adolescence.Data came from 1618 participants in the Québec Longitudinal Study of Child Development. Internalizing (depression and anxiety) and externalizing (oppositional/defiance, conduct issues, and attention deficit and/or hyperactivity) MHPs were assessed with validated questionnaires. Outcomes were self-reported past-year passive and serious suicidal ideation and suicide attempt.METHODSData came from 1618 participants in the Québec Longitudinal Study of Child Development. Internalizing (depression and anxiety) and externalizing (oppositional/defiance, conduct issues, and attention deficit and/or hyperactivity) MHPs were assessed with validated questionnaires. Outcomes were self-reported past-year passive and serious suicidal ideation and suicide attempt.Lifetime prevalence of passive suicidal ideation (13-17 years old), serious suicidal ideation, and suicide attempt (13-20 years old) were 22.2%, 9.8%, and 6.7%, respectively. Prevalence was twice as high for females as for males. Overall, rates of passive (15-17 years old; 11.8%-18.4%) and serious ideation (13-20 years old; 3.3%-9.5%) increased over time but were stable for attempt (13-20 years old; 3.5%-3.8%). In univariable analyses, all MHPs were associated with suicide-related outcomes at all ages (risk rate ratio range: 2.57-3.10 [passive ideation] and 2.10-4.36 [suicide attempt]), and associations were similar for male and female participants (sex interaction P > .05). Magnitude of associations were generally stronger for more severe suicide-related outcomes (passive ideation < serious ideation < attempt). In multivariable analyses, internalizing problems were associated with suicidal ideation, whereas both depressive and conduct symptoms were associated with attempt.RESULTSLifetime prevalence of passive suicidal ideation (13-17 years old), serious suicidal ideation, and suicide attempt (13-20 years old) were 22.2%, 9.8%, and 6.7%, respectively. Prevalence was twice as high for females as for males. Overall, rates of passive (15-17 years old; 11.8%-18.4%) and serious ideation (13-20 years old; 3.3%-9.5%) increased over time but were stable for attempt (13-20 years old; 3.5%-3.8%). In univariable analyses, all MHPs were associated with suicide-related outcomes at all ages (risk rate ratio range: 2.57-3.10 [passive ideation] and 2.10-4.36 [suicide attempt]), and associations were similar for male and female participants (sex interaction P > .05). Magnitude of associations were generally stronger for more severe suicide-related outcomes (passive ideation < serious ideation < attempt). In multivariable analyses, internalizing problems were associated with suicidal ideation, whereas both depressive and conduct symptoms were associated with attempt.Suicidal ideation and attempt were common, especially for females and youth presenting with depressive and conduct problem symptoms. Clinicians should systematically assess suicidal risk in teenagers, especially in those presenting with MHPs.CONCLUSIONSSuicidal ideation and attempt were common, especially for females and youth presenting with depressive and conduct problem symptoms. Clinicians should systematically assess suicidal risk in teenagers, especially in those presenting with MHPs.